PRESIDENTIAL ADDRESS - Current sugarcane disease scenario and management strategies - AGNIHOTRI, V.P. (Indian Phytopathology, 2002)
The current status of sugarcane diseases and the integrated disease management programme in India to control them are discussed in this review. The diseases included are red rot caused by Glomerella tucumanensis, smut caused by Ustilago scitaminea,wilt caused by Fusarium sacchari and Acremonium spp., pineapple disease caused by Ceratocystis paradoxa, eye spot caused by Drechslera sacchari, leaf scald caused by Xanthomonas albilineans, ratoon stunting caused by Clavibacter xyli subsp. xyli, grassys hoot caused by phytoplasmas and mosaic caused by sugarcane mosaic potyvirus.